2014
DOI: 10.1088/1742-5468/2014/11/p11012
|View full text |Cite
|
Sign up to set email alerts
|

On the generalized dimensions of multifractal eigenstates

Abstract: Recently, based on heuristic arguments, it was conjectured that an intimate relation exists between any multifractal dimensions, Dq and D q ′ , of the eigenstates of critical random matrix ensembles:Here, we verify this relation by extensive numerical calculations on critical random matrix ensembles and extend its applicability to q < 1/2 but also to deterministic models producing multifractal eigenstates and to generic multifractal structures. We also demonstrate, for the scattering version of the power-law b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…It would be interesting to further explore the connection between the PRBM ensemble and the truncated Anderson models to shed more light on the role of randomness and symmetry-breaking in driving a metal-insulator transition in 1 dimension, in a similar spirit to previous works [98,99].…”
Section: Appendix B: Link Between Trs Broken Model and Long-range Hopmentioning
confidence: 83%
“…It would be interesting to further explore the connection between the PRBM ensemble and the truncated Anderson models to shed more light on the role of randomness and symmetry-breaking in driving a metal-insulator transition in 1 dimension, in a similar spirit to previous works [98,99].…”
Section: Appendix B: Link Between Trs Broken Model and Long-range Hopmentioning
confidence: 83%
“…These relations have been proved to correctly describe the multifractal behavior of critical states for the PBRM model in the presence (β = 1) [21] and absence (β = 2) [22] of time reversal invariance, in a relatively wide range of the model parameters. Furthermore, it also accounts for the multifractal properties of other models showing critical behavior [21,22]. However, the PBRM model corresponding to the third of the three classical Wigner-Dyson ensembles, i.e, the symplectic case, has been left out.…”
Section: Introductionmentioning
confidence: 93%
“…More recently [21,22], this model has been used to verify the validity of existing heuristic relations, established between the multifractal properties of eigenstates and their spectra at criticality. These relations have been proved to correctly describe the multifractal behavior of critical states for the PBRM model in the presence (β = 1) [21] and absence (β = 2) [22] of time reversal invariance, in a relatively wide range of the model parameters. Furthermore, it also accounts for the multifractal properties of other models showing critical behavior [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually found that the fractal dimension as a single variable is not sufficient to capture the underlying dynamics of real-world systems. Therefore, the multifractal theory has been developed which adopts a continuous spectrum, i.e., the generalized dimension or singularity spectrum depending on the scale or region of measure [43][44][45].…”
Section: Multifractal Theorymentioning
confidence: 99%